Navigating insolvency risks in emerging markets - Aurelio GURREA-MARTINEZ, (Institutional Knowledge at Singapore Management University, 2022)
Most emerging markets have weak legal and institutional environments that generally lead to low levels of predictability and legal certainty. Moreover, the insolvency framework of most emerging markets is very inefficient, providing creditors with low recovery rates. Therefore, extending credit to companies in emerging economies may result in additional risks for lenders. This article explains how lenders can navigate some of these risks. By doing so, it is expected that, as a result of the higher level of creditor protection, companies in emerging markets will be able to have greater access to finance. Therefore, these strategies can ultimately benefit debtors and creditors and promote economic growth in emerging markets.